2015
DOI: 10.1016/j.agrformet.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of crop gross primary production (GPP): II. Do scaled MODIS vegetation indices improve performance?

Abstract: a b s t r a c tSatellite remote sensing estimates of gross primary production (GPP) have routinely been made using spectral vegetation indices (VIs) over the past two decades. The Normalized Difference Vegetation Index (NDVI), the Enhanced Vegetation Index (EVI), the green band Wide Dynamic Range Vegetation Index (WDRVI green ), and the green band Chlorophyll Index (CI green ) have been employed to estimate GPP under the assumption that GPP is proportional to the product of VI and photosynthetically active rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 73 publications
(103 reference statements)
2
15
1
Order By: Relevance
“…We found that NDVI calibrated with fAPARchl, also referred to as scaled NDVI, can improve performance of GPP estimation over original un-calibrated NDVI (Zhang, Cheng et al 2015). Our current study and other studies support the use of fAPARchl in place of fAPARcanopy in plant GPP modeling activities Croft et al 2015;Zhang et al 2014;Zhang et al 2009;Flanagan et al 2015).…”
Section: Discussionsupporting
confidence: 78%
“…We found that NDVI calibrated with fAPARchl, also referred to as scaled NDVI, can improve performance of GPP estimation over original un-calibrated NDVI (Zhang, Cheng et al 2015). Our current study and other studies support the use of fAPARchl in place of fAPARcanopy in plant GPP modeling activities Croft et al 2015;Zhang et al 2014;Zhang et al 2009;Flanagan et al 2015).…”
Section: Discussionsupporting
confidence: 78%
“…Regarding annual GPP, uncertainties are related to the apparent need of site-specific empirical scaled EVI-fAPAR functions [67], and the variability of annual LUE (affected by vegetation structural and functional traits–e.g. photosynthetic syndrome–, and soil and climatic conditions) [6772], sometimes solved by means of look-up tables (based on biome type and climatology) [37,73] or more recently by means of the carotenoid-sensitive “Photochemical Reflectance Index” (PRI) [38,74,75]. However, the accuracy of annual EVI-GPP relationships seems to improve in land covers with high annual EVI ranges and summer rainfalls [28], as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Several versions of the LUE model driven by satellite remote sensing of NDVI have been in wide use for many years [24,31,65,66]. While these models can depict broad global patterns, their agreement with local field measurements varies considerably across ecosystems or with different model formulations [67,68].…”
Section: Discussionmentioning
confidence: 99%